Assessing cell lines with inducible depletion of cohesin and condensins components through analysis of metaphase chromosome morphology - A. M. Yunusova; A. V. Smirnov; I. E. Pristyazhnuk; T. A. Shnaider; E. K. Maltseva; S. D. Afonnikova; O. A. Gusev; N. R. Battulin (Вавиловский журнал генетики и селекции)
One of the most productive strategies for finding the functions of proteins is to study the consequences of loss of protein function. For this purpose, cells or organisms with a knockout of the gene encoding the protein of interest are obtained. However, many proteins perform important functions and cells or organisms could suddenly lose fitness when the function of a protein is lost. For such proteins, the most productive strategy is to use in ducible protein degradation systems. A system of auxin-dependent protein degradation is often implemented. To use this system, it is sufficient to introduce a transgene encoding a plant-derived auxin-dependent ubiquitin ligase into mammalian cells and insert a sequence encoding a degron domain into the gene of interest. A crucial aspect of development of cell lines engineered for inducible protein depletion is the selection of cell clones with efficient  auxin-dependent degradation of the protein of interest. To select clones induced by depletion of the architectural chromatin proteins RAD21 (a component of the cohesin complex) and SMC2 (a component of the condensin complex), we propose to use the morphology of metaphase chromosomes as a convenient functional test. In this work, we obtained a series of clones of human HAP1 cells carrying the necessary genetic constructs for inducible depletion of RAD21 and SMC2. The degradation efficiency of the protein of interest was assessed by flow cytometry, Western blotting and metaphase chromosome morphology test. Based on our tests, we showed that the clones we established with the SMC2 degron effectively and completely lose protein function when induced by auxin. However, none of the HAP1 clones we created with the RAD21 degron showed complete loss of RAD21 function upon induction of degradation by auxin. In addition, some clones showed evidence of loss of RAD21 function even in the absence of induction. The chromosome morphology test turned out to be a convenient and informative method for clone selection. The results of this test are in good agreement with flow cytometry analysis and Western blotting data.